Oral health v/s general health in the elderly – an interconnected nexus- a literature review (Bangladesh Journal of Medical Science, 2024)
Introduction: Oral health and overall health have long been recognized as interconnected facets of human well-being, influencing each other in profound ways. This review highlights the essential relationship between oral health and overall health, shedding light on the bidirectional impact they exert on an individual's quality of life among the elderly group. Conversely, overall health significantly influences oral health. Chronic illnesses and immunosuppression can weaken the body's defence mechanisms against oral infections, leading to increased susceptibility to dental caries and gum diseases. Additionally, certain medications may cause dry mouth, further promoting oral health issues. Efforts to improve oral health not only enhance dental well-being but also contribute to better overall health outcomes. Regular dental check-ups, proper oral hygiene practices, and a healthy diet can positively impact systemic health, reducing the risk of certain medical conditions.Conclusion: Oral health and overall health are intricately connected, forming a dynamic interplay between the mouth and the body. Recognizing this intricate relationship is crucial for healthcare professionals and individuals alike to implement holistic approaches to maintain optimal well-being and improve health outcomes across various domains.Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S60-S65